Modeling and Application of Flexible Electronics Packaging - Huang, YongAn; Yin, Zhouping; Wan, Xiaodong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book systematically discusses the modeling and application of transfer manipulation for flexible electronics packaging, presenting multiple processes according to the geometric sizes of the chips and devices as well as the detailed modeling and computation steps for each process. It also illustrates the experimental design of the equipment to help readers easily learn how to use it. This book is a valuable resource for scholars and graduate students in the research field of microelectronics.
Advanced Electronics Packaging -- Interfacial Modeling of Flexible Multilayer Structures -- Measurement of Strength of Ultra-Thin Silicon Chip and Interfacial Fracture Energy -- Shear-Assisted Peeling -- Single-Needle Peeling -- Multi-Needle Peeling -- Conformal Peeling -- Laser Lift-Off -- Vacuum-Based Picking-up and Placing-on.
Keywords: Electronics; Optical materials; Manufactures; Mechanics, Applied; Computer simulation; Electronics and Microelectronics, Instrumentation; Optical Materials; Machines, Tools, Processes; Engineering Mechanics; Computer Modelling